PERANAN SANGGAR-SANGGAR TARI DALAM PERKEMBANGAN TARI GAYA SURAKARTA DI DAERAH ISTIMEWAYOGYAKARTA - Sumaryatmi Sumaryatmi (Greget, 2000)
Considering Yogyakarta society and Surakarta which is since breaking of Mataram (1755) always seen emulation, hence am awkwardness which [is) very draw if in this time (ml Yogyakarta in the reality dubbed (by] many Surakarta style dance, situation (017 sebaliknyapun sometime also just happened only its grol~’ith [dojnot as fast as Surakarta style dance (in] Yogyakarta.Attendance dance Surakarta style fin) Special Region Yogyakarta seems (do] not get out of Natural Sri Nail;Axis attitude (of) VII which (do] not shutting the door against brought Surakarta style dance it by its wife into its palace, and Natural Sri Nail;Axis attitude (of] VIII following its father, even [at) a period of/to hereinafter develop in the form of other him (Style Nail Alaman). Beside that Yogyakarta society attitude of[is including its governance institutes which [is) reseptif and also have more supple and free mind to accept new culture elements hence fairif Surakarta style dance can be accepted better by Yogyakarta society. But in its spreading (of) organizational perananan or grup-grup dance Surakarta style which start seen since independence pasca presumably also have big enough share. Keyword: Role, Organizational.